Institutions, contexts, and ethnic violence in comparative perspective. Issue 3 (June 2021) - Lee, Feng-yu; Lin, Tse-min
Which combinations of government structures and electoral systems create better frameworks for addressing ethnic violence? Is there any one-size-fits-all institutional solution to violent ethnic conflict? Why or why not? These questions are of substantial importance to scholars and policymakers alike, but the extant literature does not provide a systematic and thorough exploration. In this article, we argue that the effects of political institutions on ethnic violence are moderated by parameters of ethnic configurations. Through a large comparative study, we find that institutions are relevant when ethnic groups are not geographically dispersed, and whether ethnic minorities face a majority group also matters. For concentrated minorities facing a majority, semi-presidential-proportional and presidential-proportional systems are more effective in reducing violence. In cases involving concentrated minorities facing no majority, parliamentary-non-proportional systems are associated with the most intense violence. We conclude that states seeking to alleviate ethnic violence by institutional engineering must take contexts seriously.